Extraction and characterization of natural dye from arils of Celastrus paniculatus Willd. for textile application - Tejavathi, D.H.; Niranjan, R. (International Journal of Scientific Research in Biological Sciences, 2018)
Celastrus paniculatus Willd., is one of the important medicinal plants belongs to the family Celastraceae. The present study is carried out for the first time to extract natural pigment from the arils, which are of orange-red in colour. The dye was extracted with hot water boiling method. The color of the extracted dye is orange. However, the orange color changes to yellowish-orange on cotton fabric when dyed .The dye potential of the extract was evaluated by dyeing on cotton fabrics without/with mordants such as ammonium ferric sulphate, ferrous sulphate, and copper sulphate. Shades of yellow color were observed when different mordants were used. Ferrous sulphate and copper sulphate have exhibited good coordination complexes with dye molecules that have reflected in imparting bright yellow shades to the fabric. The dyed cotton fabric was tested for color fastness by light, rub and wash fastness. The fabric showed no significant changes in rub and light fastness. However, studies have showed slight fading in color when subjected to wash fastness. The spectroscopic characteristics were determined with the help of UV-Vis and FTIR. UV-Vis spectral analysis of both mordanted and unmordanted dye have revealed varied peaks for the pigments indicating different binding affinity of mordants with chromphore groups within the pigments that give different shades. Analysis of dye by Infrared spectroscopic study has displayed the presence of carotenoid content at 940cm ˉ¹. The findings disclosed that the extraction of dye from aril of Celastrus paniculatus Willd. has promising prospect in textile industry.